Books on Trial: Hold Fast and Angus, Thongs and Full-Frontal Snogging - Bartlett, Rebecca; Castleton, Jennie; Di Nardo, Bianca; Larocque, Jessica; McCoubrey, Katharine (YA Hotline, 2011)
Hold Fast: Even though it was first published in 1978, Kevin Major's Hold Fast remains a popular title in book sales and on lists of challenged books. The story is set in Newfoundland and centres around fourteen-year-old Michael who has just lost his parents in a car crash caused by a drunk driver.Angus, Thongs, and Full-Frontal Snogging is our first introduction to 14-year-old Georgia, who many readers have since revisited in Rennison's subsequent novels. This book captures the life of a teenaged girl who is like the majority of teenagers today; she hates school, experiments with make-up and ways of hiding aspects of her physical appearance that she doesn't like, and obsesses over boys.